Pengaruh Pemberian Dosis Pupuk Kandang Kambing dan Frekuensi Aplikasi Pupuk Organik Cair (POC) Mol Kohe Kambing terhadap Pertumbuhan dan Hasil Tanaman Okra (Abelmoschus Esculentus.) - moch ali ruspendi; Sunawan Sunawan; Djuhari Djuhari (AGRONISMA, 2022)
Okra is a plant that is consumed on its fruit and contains a variety of nutrients and is widely used by the community. This study aims to obtain the application dose of goat manure and liquid organic fertilizer (LOF) mol kohe goat that can increase the productivity of growth and yield of okra plants. This research was conducted on the agricultural land of the Sri Anom IV Temas farmer group, Batu District, Batu City. The study was carried out for 2 months starting from January 2022 to February 2022. The design used was a factorial randomized block design (RBD) consisting of two factors, namely goat manure (K) and liquid organic fertilizer (LOF) mol kohe goat (P). The first factor, goat manure (K) consisted of 3 treatments, namely K1 (10 tons/ha), K2 (20 tons/ha), and K3 (30 tons/ha). The second factor, liquid organic fertilizer (LOF) of goat kohe (P) consisted of 4 treatments, namely P1 (LOF 1 time), P2 (LOF 2 times), P3 (LOF 3 times), P4 (LOF 4 times). From these two factors, there were 12 treatment combinations, each treatment was repeated 3 times so that 36 experimental units were obtained. The observed growth variables were plant height and leaf area, while the yield variables observed were fruit length and fruit fresh weight. The results of this study indicate that there is a significant effect due to the interaction of goat manure dose and the frequency of application of goat mole on K2P2 plant height (20 tons/ha and LOF frequency 2 times) of 59.36 cm and K3P3 leaf area (30 tons/ha and LOF frequency 3 times) of 1575.50 cm2. While the yield variable, K2 goat manure (20 tons/ha) showed a good response to the fruit length of 11.63 cm. Meanwhile, goat manure K2 (20 tons/ha) showed a good response to fresh fruit weight of 63.02 g.Keywords : Abelmoschus esculentus., Goat Manure, Liquid Organic Fertilizer Microorganisme Local.